2021
DOI: 10.3390/rs13071306
|View full text |Cite
|
Sign up to set email alerts
|

Resolution Enhancement of Remotely Sensed Land Surface Temperature: Current Status and Perspectives

Abstract: Remotely sensed land surface temperature (LST) distribution has played a valuable role in land surface processes studies from local to global scales. However, it is still difficult to acquire concurrently high spatiotemporal resolution LST data due to the trade-off between spatial and temporal resolutions in thermal remote sensing. To address this problem, various methods have been proposed to enhance the resolutions of LST data, and substantial progress in this field has been achieved in recent years. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 110 publications
0
17
0
Order By: Relevance
“…The crucial problem is to attain a fused image with enhanced target regions and suppressed backgrounds from the spaceborne and airborne SAR images, in order to increase the target-to-clutter ratio (TCR) and improve the vessel target detection performance. Considering the issue of image fusion, some works have been carried out in the existing literature [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The most straightforward and computationally efficient fusion methods are arithmetic-based fusion approaches, such as addition fusion and multiplication fusion, but this class of fusion approaches might maintain a high level of background clutter, resulting in false alarms, or excessively suppress relatively weak targets, resulting in missed detections [10].…”
Section: Related Workmentioning
confidence: 99%
“…The crucial problem is to attain a fused image with enhanced target regions and suppressed backgrounds from the spaceborne and airborne SAR images, in order to increase the target-to-clutter ratio (TCR) and improve the vessel target detection performance. Considering the issue of image fusion, some works have been carried out in the existing literature [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The most straightforward and computationally efficient fusion methods are arithmetic-based fusion approaches, such as addition fusion and multiplication fusion, but this class of fusion approaches might maintain a high level of background clutter, resulting in false alarms, or excessively suppress relatively weak targets, resulting in missed detections [10].…”
Section: Related Workmentioning
confidence: 99%
“…Some scholars chose urban lakes as their research object, while other scholars chose urban rivers [27][28][29][30][31]. The most widely used method was field measurement, although lacking comprehensiveness and integrity of data [32][33][34][35][36][37]. It was found that the water had an obvious "cold island" effect on the surrounding area.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the relationship of fine and coarse resolution data varies diurnally, which could not be captured adequately using a static downscaling approach. Comprehensive reviews of advancement in LST downscaling methods (both spatially and temporally) along with their advantages and limitations were recently outlined by Mao et al [32] and Wu et al [33].…”
Section: Introductionmentioning
confidence: 99%